2014
DOI: 10.1037/gdn0000009
|View full text |Cite
|
Sign up to set email alerts
|

Work values and work engagement within teams: The mediating role of need satisfaction.

Abstract: Building on self-determination theory, we examined the relationship between shared work values and work engagement within teams. Specifically, we expected that employees would show higher levels of work engagement when working in teams characterized by intrinsic relative to extrinsic work values, and that this relationship can be explained by basic psychological need satisfaction. Multilevel analyses using data from 307 employees taken from 31 teams working in a variety of sectors in Belgium and the Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 79 publications
7
59
0
Order By: Relevance
“…Team members thus develop shared feelings of autonomy, competence, and relatedness while working and shared an understanding whether work is mainly seen as something important, valuable or fun or whether one feels controlled by external or internal pressures. These results add to the growing body of research, showing that motivation—as defined in SDT—may be contagious among team members (Schreurs, Van Emmerik, Van den Broeck, & Guenter, ). Our design did not permit to gain further understanding of these motivational dynamics at these different levels or to tap into the antecedents and consequences of the aspects of motivation at these different levels, but this would be an interesting route for future research.…”
Section: Discussionsupporting
confidence: 57%
“…Team members thus develop shared feelings of autonomy, competence, and relatedness while working and shared an understanding whether work is mainly seen as something important, valuable or fun or whether one feels controlled by external or internal pressures. These results add to the growing body of research, showing that motivation—as defined in SDT—may be contagious among team members (Schreurs, Van Emmerik, Van den Broeck, & Guenter, ). Our design did not permit to gain further understanding of these motivational dynamics at these different levels or to tap into the antecedents and consequences of the aspects of motivation at these different levels, but this would be an interesting route for future research.…”
Section: Discussionsupporting
confidence: 57%
“…The concept of engaging leadership was developed by Schaufeli () and SDT (Deci & Ryan, ) was chosen as the theoretical foundation because research showed that the fulfillment of basic psychological needs at work, as stipulated by SDT, is positively related to work engagement (Schreurs, van Emmerik, Van den Broeck, & Guenter, ; Sulea, van Beek, Sarbescu, Virga, & Schaufeli, ; Van den Broeck, Vansteenkiste, De Witte, & Lens, ). When employees' basic needs for competence, relatedness, and autonomy are satisfied they are more likely to be engaged at work, that is.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, in fostering workplace creativity, HR managers need to consider the importance of diverse individual work values. Although work values were not directly investigated in this study, job characteristics and organizational context factors closely relate to individual work values, as indicated by research on employees' psychological needs, intrinsic motivation, and job satisfaction (Caricati et al 2014;Schreurs et al 2014). As James and Drown (2012) noted, scholars and practitioners ought to take into account individual differences towards work values when examining individual creativity.…”
Section: Discussionmentioning
confidence: 92%
“…; Schreurs et al. ). As James and Drown () noted, scholars and practitioners ought to take into account individual differences towards work values when examining individual creativity.…”
Section: Discussionmentioning
confidence: 97%